Beekeeping New Challenges - Eduardo Rebolledo Ranz, Ramón (IntechOpen, 2020)
This book comes to fill a void in beekeeping research worldwide since it addresses a series of issues of great contingency such as the problem and control of varroa, the management of the American foulbrood, management of hives to perform an adequate transhumance, and the way of handling Brazilian beekeeping.It is a text that is aimed at scientists, producers, undergraduate and graduate students, companies, and the general public who handle hives at a professional or amateur level that have from one to many hives.The book corresponds to the authors' experience of many years who with their contributions will improve the productive activity of beekeeping in the world concert.